2020
DOI: 10.5114/aoms.2019.88625
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hyperbilirubinaemia on synaptic plasticity in the dentate gyrus region of the rat hippocampus in vivo

Abstract: Introduction: The aim of our study is to investigate the effect of hyperbilirubinaemia on synaptic plasticity in the dentate gyrus (DG) region of the rat hippocampus. Material and methods: Seven-day-old healthy Sprague Dawley (SD) rats were randomly divided into a control group and an experiment group (n = 20 in each group). The input/output (I/O) functions, paired-pulse reactions (PPR), excitatory postsynaptic potential (EPSP), and population spike (PS) amplitude were measured in the DG area of both groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is well accepted that memory is intimately associated with the plasticity of neuronal synapses in the hippocampus [ 66 ]. In our study, the granular cells of the dentate gyrus region were significantly fewer in diabetic, exercised, and metformin-treated groups compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that memory is intimately associated with the plasticity of neuronal synapses in the hippocampus [ 66 ]. In our study, the granular cells of the dentate gyrus region were significantly fewer in diabetic, exercised, and metformin-treated groups compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“… Chang et al (2009) reported that long-term potentiation (LTP) and long-term depression (LTD) induction were impaired by UCB (1–10 μM for 24–48 h) in a time- and concentration-dependent manner ( Chang et al, 2009 ), possibly through calpain-mediated proteolytic cleavage of NMDA receptor subunits. In vivo studies have also demonstrated that hyperbilirubinemia can cause LTP inhibition ( Zhang et al, 2003 ; Yang et al, 2020 ) and the impairment of input/output functions and paired-pulse reactions, which reflect the basal synaptic response and short-term synaptic plasticity ( Yang et al, 2020 ).…”
Section: Bilirubin and Synapsesmentioning
confidence: 99%
“…It is well known that a high level of ammonia is toxic to the ner-vous system; it results in encephalopathy, and eventually coma and death [39]. Moreover, the hyperbilirubinemia that may be encountered in patients with hepatic encephalopathy induced impairment of memory through impairing synaptic plasticity in the hippocampus via disturbing longterm potentiation that facilitates information storage at the synaptic level and is considered the chief component of memory consolidation [40]. Acetaminophen can easily penetrate the blood brain barrier, activating the neuronal cytochrome P450 2E1, generating toxic metabolites such as N-acetyl-p-benzoquinoneimine (NAPQI), which decreases glutathione, ascorbic acid, superoxide dismutase levels, resulting in oxidative stress and neurotoxicity [3].…”
Section: Number Of Dark Neuronsmentioning
confidence: 99%